Web-based interventions supporting the mental health of adolescents with depression - Anttila, Katriina (fi=Turun yliopisto|en=University of Turku|, 2018)
The aim of this study was to enhance the knowledge of potential of web-based interventions that support the mental health of adolescents with depression. The data were collected 2008–2017. A mixed methods study in three phases was conducted. First, a systematic literature review was carried out to describe web-based interventions and examine their impact. Second, the needs of adolescents, based on their own concerns, hopes and social relationships, were explored from their perspective when they visited adolescent psychiatric outpatient clinics. Third, feedback on the web-based support system was gathered. Qualitative data were analyzed with thematic analysis and quantitative data with statistical methods. In the review, 22 studies (27 articles) were included. The web-based interventions were diverse in their content. Further, 15 studies (16 articles) were included in the meta-analysis. Depression symptoms were found to have reduced in intervention group compared to control group, after intervention (p=.02) and when measured 6 months after intervention (p=.01). The reduce was not statistically significant at 3– 5 month’s follow-up. Adolescents in the intervention group left the study earlier than those in control group. The adolescents (n=70) described multiple concerns in their lives, but also hopes. Their (n = 29) social relationships varied in extent and quality. Adolescents (n=46) provided positive feedback on web-based support system and found it to be reliable and appropriate for them. Some adolescents had difficulties with the system and did not experience getting help. Ideas to increase interaction and add detailed information about depression on sites were given. Web-based interventions are potentially useful for supportingmental health among adolescents with depression and complementing current services. Positive experiences by adolescents encourage the use, but those interventions are not suitable for everyone. The different needs of adolescents with depression should be taken into account when developing web-based interventions or planning treatment for them.

Verkkopohjaiset interventiot masentuneiden nuorten mielenterveyden tukena Tutkimuksen tavoitteena oli saada tietoa verkkopohjaisten interventioiden mahdollisuudesta tukea masentuneiden nuorten mielenterveyttä. Aineisto kerättiin 2008–2017. Tutkimus toteutettiin kolmivaiheisena monimenetelmätutkimuksena. Ensimmäisessä vaiheessa tehtiin systemaattinen kirjallisuuskatsaus interventioiden kuvauksista ja vaikuttavuudesta. Toisessa vaiheessa selvitettiin nuorten tarpeita perustuen huoliin, toiveisiin ja ihmissuhteisiin heidän ollessa asiakkaina nuorisopsykiatrian poliklinikoilla. Kolmannessa vaiheessa kuvattiin nuorten antama palaute verkkopohjaisesta tukiohjelmasta. Laadulliset aineistot analysoitiin käyttäen teema-analyysia ja määrälliset aineistot tilastollisilla menetelmillä. Katsaukseen valittiin 22 tutkimusta (27 artikkelia). Verkkopohjaiset interventiot erosivat keskenään sisällöiltään. Meta-analyysiin valittiin 15 tutkimusta (16 artikkelia). Masennusoireet vähenivät interventioryhmässä kontrolliryhmään verrattuna heti intervention jälkeen (p=.02) ja yli 6 kk seurannassa (p=.01). Vaikutus ei ollut tilastollisesti merkitsevä 3–5 kk seurannassa. Nuoret keskeyttivät tutkimuksen interventioryhmässä useammin verrattuna kontrolliryhmään. Nuoret (n=70) kuvasivat lukuisia elämäänsä liittyviä huolia, mutta myös toiveita. Heidän (n=29) sosiaaliset suhteensa vaihtelivat määrältään ja laadultaan. Nuoret (n=46) antoivat palautetta verkkopohjaisen tukiohjelman käytöstä ja kokivat sen pääosin myönteisenä ja luotettava sekä heille tarkoitetuksi. Osalla nuorista oli vaikeuksia käyttää ohjelmaa ja he eivät kokeneet saavansa siitä apua. Kehittämisehdotukset liittyivät vuorovaikutuksen lisäämiseen ja masennukseen liittyvän tiedon tarkentamiseen. Verkkopohjaiset interventiot tarjoavat käyttökelpoisen menetelmän masentuneiden nuorten mielenterveyden tukemiseksi ja palveluiden täydentämiseksi. Nuorten myönteiset kokemukset tukevat verkkopohjaisten interventioiden käyttöä, mutta silti ne eivät sovi kaikille. Erilaiset tarpeet tulee ottaa huomioon, kun kehitetään verkkopohjaisia interventioita tai suunnitellaan hoitoa masentuneille nuorille.